Parameter optimization for fly ash geopolymer mixtures: molarity, silica modulus, and solution/binder influence - Ana Laura Lopes de Matos Riscado; Carlos Maurício Fontes Vieira; Sergio Neves Monteiro; Afonso Rangel Garcez de Azevedo; Markssuel Teixeira Marvila (Scientific Reports)
Abstract The growing environmental concerns associated with the production of Portland cement—such as high energy consumption, raw material depletion, and CO₂ emissions—underscore the urgent need for more sustainable alternatives. In this context, geopolymers based on fly ash have emerged as a promising substitute due to their lower environmental impact and favorable mechanical properties. This study aims to develop and validate a dosage methodology for fly ash-based geopolymers using key compositional parameters: water-to-binder ratio (w/b), aggregate-to-binder ratio (m), alkaline solution molarity (M), and silica modulus (Ms). The main innovations and justifications for the work are related to the need to develop a simple methodology for dosing and defining the proportion of geopolymers. Geopolymer mixtures were prepared and cured at 25 °C and 60 °C, and evaluated for compressive strength. The results revealed a strong linear correlation between compressive strength and w/b ratio (R² = 0.9952), as well as a quadratic relationship with the aggregate/binder ratio (R² = 0.9927). Similar correlations were observed for molarity (R² = 0.9009) and silica modulus (R² = 0.8956). Notably, thermal curing significantly enhanced mechanical performance, supporting the role of temperature in promoting geopolymerization. The highest compressive strength achieved experimentally was 50.19 MPa, while the predictive model yielded 46.99 MPa, with an error margin of only 6.3%. Complementary analyses using isothermal calorimetry, X-ray diffraction (XRD), and scanning electron microscopy (SEM) confirmed the formation of sodalite phases, indicating effective geopolymerization. These findings demonstrate that the proposed methodology offers a reliable and practical framework for optimizing and predicting the mechanical performance of fly ash-based geopolymers, contributing significantly to advancing sustainable construction materials with consistent performance and lower environmental impact.